Упростите выражение: 1) (2х-3y)(2x+3y)+(3x+2y)(3x-2y); 2) (x+1)²-(x-3)(x+3); 3) (y-4)(y+3)-(y-6)². [8 класс]

2

Ответы и объяснения

  • ayka89
  • почетный грамотей
2011-09-03T12:55:01+00:00

1) (2х-3y)(2x+3y)+(3x+2y)(3x-2y) = 4x² - 9y² + 9x² - 4y² = 13x² - 13y² = 13(x² - y²) = 13(x - y)(x + y)

2)(x+1)²-(x-3)(x+3) = x² + 2x + 1 - x² + 9 = 2x + 10 = 2(x + 5)

3)(y-4)(y+3)-(y-6)² = y² + 3y - 4y - 12 - y² + 12y - 36 = 11y - 48

2011-09-03T13:59:30+00:00

1) (2х-3у)(2х+3у)+(3x+2y)(3x-2y)=4х²-9у²+9х²-4у² = 13х² - 13у²

2) (x+1)²-(x-3)(x+3)= (х+1)² - (х²-9)= х² + 2х + 1 - х² + 9 = 2х + 10

3)(y-4)(y+3)-(y-6)²= (y-4)(y+3) - (у² - 12у + 36 ) = у² + 3у - 4у -7 -у² +12у -36= 11у - 29 

 

Использовала формулы сокращённого умножения: 

а² - в² = (а-в)(а+в)

(а+в)² = а² - 2ав + в²